No-tillage practice enhances soil total carbon content in a sandy Cyperus esculentus L. field - Wang, Cong; Hu, Yuxiang; Wu, Hui; Wang, Zhirui; Cai, Jiangping; Liu, Heyong; Ren, Wei; Yang, Ning; Wang, Zhengwen; Jiang, Yong; Li, Hui (Ecological processes, 2025)
Background No-tillage (NT) is a widely used field management to reduce soil erosion and degradation and is suggested to be beneficial for enhancing soil carbon (C) sequestration capacity. Nonetheless, the effects of NT on soil total carbon (TC) content in aeolian sandy soils are not extensively explored, and the underlying mechanisms are not clear. In our field experiments, the influence of NT and conventional tillage (CT) on sandy soil was studied. Methods We estimated the changes in soil TC in response to NT practice in a Cyperus esculentus L. field located at semi-arid Horqin sandy land, China. To unravel the underlying mechanisms, plant traits, soil properties and soil microbial characteristics were measured in parallel. The variations in soil bacterial community structure were investigated by 16S rRNA amplicon sequencing. The functionality of soil bacterial community was predicted based on OTU tables by using PICRUSt2. Results NT increased soil TC content in this sandy agroecosystem within a short-term experimental period, compared to CT. The underlying mechanisms might rely on three aspects. First, NT increased soil TC content through increasing photosynthesis and plant biomass, and thus, the plant-derived dissolved organic C. Second, NT increased the C immobilized in soil microbial biomass by increasing microbial C demands and C use efficiency. Third, NT increased the dominance of oligotrophic members in bacterial communities by decreasing available nutrient levels, which is associated with the recalcitrance and stability of the soil organic carbon. Conclusions The present study enriched our knowledge on the changes in the plant-soil-microbe continuum in response to NT in a semi-arid sandy agroecosystem. Still, this study provides a reference for modifying tillage practices to benefit crop yield as well as soil C sequestration.